(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
This article explores the significance of promoting teamwork and collaboration between dentists and dental assistants in modern dental practices. Effective collaboration enhances patient care, practice efficiency, and job satisfaction among dental professionals. Clear delineation of roles, open communication, and mutual respect are crucial components of successful teamwork. Cross-training and professional development opportunities empower dental assistants to contribute effectively to patient care. Collaboration in patient treatment planning and delivery optimizes clinical outcomes and patient satisfaction. Cultivating a positive work environment fosters teamwork and enhances practice culture. By embracing collaborative practices, dental teams can achieve excellence in patient care while fostering a supportive and cohesive work environment.